2012
DOI: 10.1002/ijc.27925
|View full text |Cite
|
Sign up to set email alerts
|

Interim analysis of START: Study in asia of the combination of TACE (transcatheter arterial chemoembolization) with sorafenib in patients with hepatocellular carcinoma trial

Abstract: Transarterial chemoembolization (TACE) represents a first-line noncurative therapy for hepatocellular carcinoma (HCC). Sorafenib, a multikinase inhibitor, has been shown to be effective and safe monotherapy in patients with advanced HCC and the current study reports the interim results of a prospective Phase II, open label, trial investigating the safety and efficacy of the combination of sorafenib and conventional TACE in patients from the Asia-Pacific region with intermediate HCC. Patients with histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 39 publications
4
48
1
Order By: Relevance
“…Nagano et al noticed that the overall median progression-free survival (PFS) of advanced HCC was 2.0 months (40). In addition, the association between sorafenib therapy and longer DFS is largely concordant with previous studies in patients with HCC (25,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In a pilot study by Wang et al (25) that included 31 patients at a high risk of recurrence, sorafenib therapy following hepatic resection significantly improved the time to recurrence as well as the recurrence rate.…”
Section: Discussionsupporting
confidence: 61%
“…Nagano et al noticed that the overall median progression-free survival (PFS) of advanced HCC was 2.0 months (40). In addition, the association between sorafenib therapy and longer DFS is largely concordant with previous studies in patients with HCC (25,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In a pilot study by Wang et al (25) that included 31 patients at a high risk of recurrence, sorafenib therapy following hepatic resection significantly improved the time to recurrence as well as the recurrence rate.…”
Section: Discussionsupporting
confidence: 61%
“…Similar clinical studies are currently being conducted globally [94,95]. It is hoped that the findings from these studies corroborate the positive results obtained from the Asia-Pacific region [93].…”
Section: Combination With Targeted Chemotherapysupporting
confidence: 79%
“…Given the different modes of actions between the kinase inhibitor (sorafenib) and the cytotoxic agent (doxorubicin), it is perfectly reasonable to evaluate the combination of these two classes of drug and assess the clinical benefits that may bring to HCC patients. Excitingly, a recent phase II study revealed the combined use of sorafenib and doxorubicin (administrated as conventional TACE) in patients from the Asia-Pacific region with intermediate HCC [93]. The disease control rate and overall response rate were reported to be 91.2 % and 52.4 %, respectively.…”
Section: Combination With Targeted Chemotherapymentioning
confidence: 99%
“…improved survival benefit in patients with stage B disease receiving a combination of sorafenib and transcatheter arterial chemoembolization (TACE) (Chung et al, 2013;Park et al, 2012).…”
Section: Sorafenib Continuation After First Disease Progression Couldmentioning
confidence: 99%